Double joy for gutsy twins: Talented tennis prodigies reign supreme in singles category of Kedah challenge - Noh, Dasheer (The Star (Metro North), 2014)
SHAMIRUL Shahril Adam Das and his twin sister Suhana Sofia Adam Das (Selangor) won back-to-back titles in the Mamee-Junior Tennis circuit.They successfully defended their respective titles in the fourth leg Tennis-Malaysia tournament organised by the Kedah Tennis Association at the Universiti Utara Malaysia courts in Sintok.